Sericin enhances the developmental competence of heat‐stressed bovine embryos. Issue 8 (18th July 2018) - Khatun, Hafiza; Egashira, Junki; Sakatani, Miki; Takenouchi, Naoki; Tatemoto, Hideki; Wada, Yasuhiko; Yamanaka, Ken‐ichi
Abstract : We investigated the effects of sericin on the developmental competence of bovine embryos exposed to heat stress (HS). Putative zygotes were cultured with sericin and subjected to HS (40.5°C for 6 hr) on Day 2 or 7 followed by continuous culture at 38.5°C until Day 8. Day 2 HS significantly decreased blastocyst development on Day 8 as well as mitochondrial activity, and significantly increased the amount of intracellular reactive oxygen species and terminal deoxynucleotidyl transferase biotin‐dUTP nick end labeling (TUNEL)‐positive cells, whereas Day 7 HS only significantly decreased mitochondrial activity and increased the number of TUNEL‐positive cells in Day 8 blastocysts. These detrimental effects were neutralized by sericin supplementation. Next, to investigate the potential production of blastocysts with high viability in terms of thermotolerance, embryos were cultured with sericin until Day 7, and then exposed to HS in the sericin‐free medium. TUNEL‐positive cell numbers were significantly lower in blastocysts produced by sericin culture than in control blastocysts. Transcript abundance for HSPA1A and BAX was significantly decreased but IFNT2 levels were increased in blastocysts produced by sericin culture. In conclusion, these findings demonstrate the anti‐oxidative and anti‐apoptotic activities of sericin, and the potential use of sericin to produce embryos with high viability in vitro.